Prognostic value of tumor necrosis at CT in diffuse large B-cell lymphoma. Issue 3 (March 2015) - Adams, Hugo J.A.; de Klerk, John M.H.; Fijnheer, Rob; Dubois, Stefan V.; Nievelstein, Rutger A.J.; Kwee, Thomas C.
Highlights: CT is compulsory for staging newly diagnosed DLBCL. Approximately 13.7% of DLBCL patients have tumor necrosis at CT. Tumor necrosis status at CT is not associated with any NCCN-IPI factor. Patients with tumor necrosis at CT have a significantly worse outcome. Abstract: Objective: To determine the prognostic value of tumor necrosis at computed tomography (CT) in newly diagnosed diffuse large B-cell lymphoma (DLBCL). Materials and methods: This retrospective study included 51 patients with newly diagnosed DLBCL who had undergone both unenhanced and intravenous contrast-enhanced CT before R-CHOP (rituximab, cyclophosphamide, hydroxydaunorubicin, oncovin and prednisolone) chemo-immunotherapy. Presence of tumor necrosis was visually and quantitatively assessed at CT. Associations between tumor necrosis status at CT and the National Comprehensive Cancer Network (NCCN) International Prognostic Index (IPI) factors were assessed. Cox regression analysis was used to determine the prognostic impact of NCCN-IPI scores and tumor necrosis status at CT. Results: There were no correlations between tumor necrosis status at CT and the NCCN-IPI factors categorized age ( ρ  = −0.042, P  = 0.765), categorized lactate dehydrogenase (LDH) ratio ( ρ  = 0.201, P  = 0.156), extranodal disease in major organs ( φ  = −0.245, P  = 0.083), Ann Arbor stage III/IV disease ( φ  = −0.208, P  = 0.141), and Eastern Cooperative Oncology Group (ECOG) performance status ( φ  = 0.015, P  = 0.914). In the multivariate Cox proportional hazards model, only tumor necrosis status at CT was an independent predictive factor of progression-free survival ( P  = 0.003) and overall survival ( P  = 0.004). Conclusion: The findings of this study indicate the prognostic potential of tumor necrosis at CT in newly diagnosed DLBCL.